The impact of seasonal varied human activity on characteristics and sources of heavy metals in metropolitan road dusts - Men, Cong; Liu, Ruimin; Wang, Qingrui; Guo, Lijia; Shen, Zhenyao (The Science of the total environment, 2018)
Due to significant human activity, road dust is becoming contaminated by heavy metals in many cities. To comprehensively investigate the variation of contamination level and sources of heavy metals in road dust, 10 heavy metals in road dust samples from Beijing, China, in both summer and winter, were evaluated by spatial analysis using geographic information system (GIS) mapping technology and the positive matrix factorization (PMF) Model. Although the concentrations of some heavy metals between summer and winter had similarities, the differences of others and spatial distributions of heavy metals between summer and winter were considerable. The mean concentrations of As, Cd, Cr, Cu, and Fe were lower in winter, while those of Hg, Mn, Ni, Pb, and Zn were higher. According to the values of the Pollution Index (PI) and Nemerow Integrated Pollution Index (NIPI), there were no obvious differences between summer and winter, but the range between different sites in winter was nearly twice that of summer. Based on the PMF model, four sources of heavy metals in the dust samples were identified. Although the types of sources were consistent, the relative contributions of each source differed between summer and winter. Non-exhaust vehicle emissions was the most important source in summer (34.47 wt%), while fuel combustion contributed the largest proportion to the total heavy metals in winter (32.40 wt%). The impact of each source also showed spatial variation different trends in summer and winter. With the alteration of seasons, intensity of human activities also changed, such as the number of tourists, energy needs for building temperature regulation, construction, and the amount of pesticides and fertilizer. That might be the reason for the variation of heavy metal concentrations and relative contribution of their sources between summer and winter. [Display omitted] •Impact of human activity on heavy metals in road dusts was studied in two seasons.•Pollution levels and source types were similar, while source contribution varied.•Dominant source was traffic exhaust in summer, while fuel combustion in winter.•Source contribution and impact area changed with the variation of human activities.